Modelling virtual heritage environments using hierarchy-embedded virtual objects - Wan Mohd Rizhan, Wan Idris; Mat Atar, Mat Amin; Mohd Sufian, Mat Deris (2015)
Nowadays, heritage is eventually inexistence, inaccessible and design decision due to the constructions of new buildings and sites. Various techniques in virtual reality have been proposed in producing virtual heritage. Improper management of virtual heritages in their virtual environments in terms of location and link may cause delivering information unsystematically. This paper is purposed to model virtual heritage environments for one case study of sheltered pavilion using Hierarchy-Embedded Virtual Objects technique. This technique is a hierarchical, tree-structured approach that emulates a tree structure with a set of linked nodes. Three different virtual heritage environments have been published through the tree structure in HEVO Editor. Organizing Editor has enables virtual heritages to be managed in terms of location and link. The resulted virtual heritage environments can be visualized, interacted and navigated through Viewing Editor. These virtual heritage environments are believed to be significant for learning the VH and presenting the values inculcated inside them. Challenges of the modelling technique, research quantification, modelling goals and VH attractions also have been discussed for advanced consideration to model VH.